Megakaryocytes Are Regulators of the Tumor Microenvironment and Malignant Hematopoietic Progenitor Cells in Myelofibrosis - Varricchio, Lilian; Hoffman, Ronald (Frontiers in Oncology, 2022)
Megakaryocytes (MKs) are multifunctional hematopoietic cells that produce platelets, serve as components of bone marrow (BM) niches that support the development of hematopoietic stem and progenitor cell (HSPC) and provide inflammatory signals. MKs can dynamically change their activities during homeostasis and following stress, thereby regulating hematopoietic stem cell (HSC) function. Myelofibrosis (MF) is a progressive chronic myeloproliferative neoplasm (MPN) characterized by hyperactivation of JAK/STAT signaling and MK hyperplasia, which is associated with an aberrant inflammatory signature. Since JAK1/2 inhibitor alone is incapable of depleting the malignant HSC clones or reversing BM fibrosis, the identification of mechanisms that cooperate with MF JAK/STAT signaling to promote disease progression might help in developing combination therapies to modify disease outcomes. Chronic inflammation and MK hyperplasia result in an abnormal release of TGFβ1, which plays a critical role in the pathobiology of MF by contributing to the development of BM fibrosis. Dysregulated TGFβ signaling can also alter the hematopoietic microenvironment supporting the predominance of MF-HSCs and enhance the quiescence of the reservoir of wild-type HSCs. Upregulation of TGFβ1 levels is a relatively late event in MF, while during the early pre-fibrotic stage of MF the alarmin S100A8/S100A9 heterocomplex promotes pro-inflammatory responses and sustains the progression of MF-HSCs. In this review, we will discuss the recent advances in our understanding of the roles of abnormal megakaryopoiesis, and the altered microenvironment in MF progression and the development of novel combined targeted therapies to disrupt the aberrant interplay between MKs, the BM microenvironment and malignant HSCs which would potentially limit the expansion of MF-HSC clones.